(Mis)reading ‘Sharia’ into the Ugandan Succession Act? Edirisa Miyingo v Ismail Ssempijja and Another (Civil Appeal 189 of 2019) [2025] UGCA 273 (19 August 2025) - Jamil Ddamulira Mujuzi (Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto, 2026)
Section 1 of the Succession Act provides that, “except as provided by this Act, or by any other law for the time being in force, the provisions of this Act shall constitute the law of Uganda applicable to all cases of intestate or testamentary succession.” The phrase “any other law” refers to written law. During the drafting of the Succession (Amendment) Act 2022, a proposal that the Succession Act should provide for circumstances in which Sharia would govern the estates of Muslims who die intestate was considered but not approved by Parliament. Consequently, the Succession Act remains the sole law governing the distribution of the estate of any person who dies intestate. Notwithstanding this legislative position, in Edirisa Miyingo v Ismail Ssempijja and Another (2025) the Court of Appeal held that the distribution of the estate of a Muslim who had died intestate in accordance with Sharia was not contrary to the Succession Act, despite acknowledging that Sharia is unwritten law. This article argues, inter alia, that the Court’s approach is inconsistent with the drafting history of the Succession Act and amounts to an impermissible reading-in of an exception that Parliament deliberately declined to enact.